Thermodynamic and Process Modeling of CO2 Chemical Absorption Process Using Aqueous Monoethanolamine and Enzymatic Potassium Carbonate Solvents: Validation and Comparative Analysis - Anthoula Plakia; Christina Papaioannou; Panagiotis Grammelis (Energies)
Carbon dioxide is a major contributor to global warming, with chemical absorption using aqueous monoethanolamine (MEA) being the most widespread technology for CO2 capture. However, due to the limitations of MEA, alternative solvents should be examined. In this work, CO2 capture using potassium carbonate promoted by the enzyme carbonic anhydrase is compared to the conventional aqueous MEA solvent. For that purpose, models for both solvents are developed, focusing on accurate thermodynamic modeling of the mixtures and simulation of the processes. As a first step, the thermodynamic modeling of CO2-H2O-MEA and CO2-H2O-K2CO3 mixtures is examined. Parameters of the electrolyte non-random two-liquid (eNRTL) model in Aspen Plus V11 are updated through regression against binary and ternary solubility and heat capacity experimental data. The regression results are satisfactory. Afterwards, the updated eNRTL is applied to the development of rate-based process models, which are validated against experimental results from pilot plants presented in the literature to ensure their accuracy. Finally, the two solvents are compared, with enzymatic potassium carbonate emerging as a promising alternative to MEA for CO2 capture. At optimized conditions and an 85% capture efficiency, the reboiler duties are 3.5 MJ/kg for enzymatic potassium carbonate and 4.2 MJ/kg CO2 for MEA.